SUSTAINABILITY REPORTING DAN PROFITABILITAS (STUDI PADA PEMENANG INDONESIAN SUSTAINABILITY REPORTING AWARDS) - Dewi, Komang Eva Cyntia; Sudana, I Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 1 (2015))
The purpose of this study is to determine the effect of sustainability reporting disclosure intensity to return on assets that is represented by return on assets. This study used a sample of 28 companies winning Indonesian Sustainability Reporting Awards. The examination of hypothesis is conducted using simple linear regression analysis. This study conclude that the intensity of the disclosure of sustainability reporting has positive effect to the profitability of companies. Significance of the positive effect observed at the year the sustainability reporting is published. Meanwhile, in the year after the publication, no significant effect can be observed.
Keywords: sustainability reporting, profitability, return on assets